A causal model to assess the influence of supply chain 4.0 on Moroccan companies’ performance - Sassi, Abdellah; Ben Ali, Mohamed; Oullada, Oumaima; Adri, Ahmed (International Journal of Advances in Applied Sciences, 2025)
Although supply chain 4.0 (SC 4.0) has been widely adopted by major industries globally, particularly in developed countries, Moroccan industries, including key sectors like automotive and aeronautical, are just beginning to give this concept the attention it deserves, therefore, the examination of the impact of this new concept on the companies’ performance has not been presented in the literature review. This paper presents a conceptual model used to evaluate the impact of the SC 4.0 levers (purchase and supply, production, storage and distribution, and sales and after-sales) on companies’ financial and organizational performance using the statistical package for the social sciences (SPSS) version 26.0, the goal is to investigate the relationship between the SC 4.0 levers as a mean construct in one hand, and the other hand, financial and organizational performance as results constructs, the findings in this research paper confirm the significant and positive relationship between these constructs, aligning with what was cited in the literature review.